Estrogen deficiency reduces maximal running capacity and affects serotonin levels differently in the hippocampus and nucleus accumbens in response to acute exercise - Lee, Earric; Nissinen, Tuuli A.; Ylä-Outinen, Laura; Jalkanen, Aaro; Karppinen, Jari E.; Vieira-Potter, Victoria Jeanne; Lipponen, Arto; Karvinen, Sira (Frontiers in Neuroscience, 2024)
Introduction: Estrogen deficiency is associated with unfavorable changes in body composition and metabolic health. While physical activity ameliorates several of the negative effects, loss of ovarian function is associated with decreased physical activity levels. It has been proposed that the changes in brain neurochemical levels and /or impaired skeletal muscle function may underlie this phenomenon. Methods: We studied the effect of estrogen deficiency induced via ovariectomy (OVX) in female Wistar rats (n=64). Rats underwent either sham or OVX surgery and were allocated thereafter into four groups matched for body mass and maximal running capacity: sham/control, sham/max, OVX/control, and OVX/max, of which the max groups had maximal running test before euthanasia to induce acute response to exercise. Metabolism, spontaneous activity, and maximal running capacity were measured before (PRE) and after (POST) the surgeries. Three months following the surgery, rats were euthanized, and blood and tissue samples harvested. Proteins were analyzed from gastrocnemius muscle and retroperitoneal adipose tissue via Western blot. Brain neurochemical markers were measured from nucleus accumbens (NA) and hippocampus (HC) using ultra-high performance liquid chromatography. Results: OVX had lower basal energy expenditure and higher body mass and retroperitoneal adipose tissue mass compared with sham group (p≤0.005). OVX reduced maximal running capacity by 17% (p=0.005) with no changes in muscle mass or phosphorylated form of regulatory light chain (pRLC) in gastrocnemius muscle. OVX was associated with lower serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA) level in the NA compared with sham (p=0.007). In response to acute exercise, OVX was associated with low serotonin level in the HC and high level in the NA (p≤0.024). Discussion: Our results highlight that OVX reduces maximal running capacity and affects the response of brain neurochemical levels to acute exercise in a brain region-specific manner. These results may offer mechanistic insight into why OVX reduces willingness to exercise.